The clinical value of the PRECISE-DAPT score in predicting long-term prognosis in patients with acute myocardial infarction. (August 2020) - Ando, Takuya; Nakazato, Kazuhiko; Kimishima, Yusuke; Kiko, Takatoyo; Shimizu, Takeshi; Misaka, Tomofumi; Yamada, Shinya; Kaneshiro, Takashi; Yoshihisa, Akiomi; Yamaki, Takayoshi; Kunii, Hiroyuki; Takeishi, Yasuchika
Abstract: Background: The predicting bleeding complications in patients undergoing stent implantation and subsequent dual antiplatelet therapy (PRECISE-DAPT) score predicts the risk of bleeding in patients treated with dual antiplatelet therapy after percutaneous coronary intervention. Although the PRECISE-DAPT score is expected to be useful beyond its original field, long-term prognostic value of this score in patients with acute myocardial infarction (AMI) remains unclear. In the current study, we aimed to investigate the performance of the PRECISE-DAPT score in predicting the long-term prognosis in patients with AMI. Methods and results: Consecutive 552 patients with AMI, who had been discharged from our institution, were enrolled. We divided the patients into three groups, based on their PRECISE-DAPT scores: the low (PRECISE-DAPT < 17), intermediate (17–24) and high (≥25) score groups. Kaplan-Meier analysis (mean follow-up 1424 days) revealed that all-cause mortality increased most steeply in the high score group followed by the intermediate and low score groups (P < 0.001). After adjusting for possible confounding factors, mortality of the intermediate or high score groups were higher than those of low score group (HR 2.945, 95% CI 1.182–7.237, P = 0.020, and HR 5.567, 95% CI 2.644–11.721, P < 0.001, respectively). Conclusions: In patients with AMI, a high PRECISE-DAPT score was associated with higher long-term all-cause mortality. PRECISE-DAPT score is useful for predicting all-cause mortality, as well as risk stratification of bleeding.